Evaluation of the Implementation of the Corporate Social Responsibility (CSR) Program in the Empowerment of SMEs at PT Pertamina Patra Niaga’s Tanjung Gerem Fuel Terminal in Cilegon - Nauli, Rudi Martahi; Amiruddin , Suwaib; Yulianti , Rina (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to evaluate the implementation of the Corporate Social Responsibility (CSR) Program of PT Pertamina Patra Niaga Fuel Terminal Tanjung Gerem in empowering Micro, Small, and Medium Enterprises (MSMEs) in Gerem Village, Cilegon City. The research uses a descriptive qualitative method with an evaluative approach based on OECD/DAC criteria which include relevance, coherence, effectiveness, efficiency, impact, and sustainability. Data collection was carried out through in-depth interviews, observations, documentation studies, and data triangulation, then analyzed using the help of NVivo software. The results of the study show that the CSR program has provided positive benefits for fostered MSMEs through increasing business capacity, legality, product quality, and increasing income. However, various obstacles are still found, such as limitations in production, processing, marketing, and suboptimal collaboration between companies, local governments, and the community. In addition, the sustainability of the program still faces challenges in the form of the lack of sustainable market certainty for MSME products so that marketing still depends on promotional activities and exhibitions. Although administratively the program has achieved the set targets, the evaluation shows the need to strengthen governance, increase synergy between stakeholders, and develop market access so that CSR programs can have a more sustainable impact on MSME empowerment and community welfare.